HUBUNGAN KEPERCAYAAN DIRI DENGAN PERILAKU ASERTIF PADA ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 KOTA PEKANBARU - Pardede, Eka Sartika; Chairilsyah, Daviq; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This Research is based on low of self-confidence in children. Self-confidence has an important role in determining one's behavior. Good self-confidence will have a positive influence on the development of child assertive behavior. Without being supported by traits that reflect assertive behavior, the child will find it difficult to achieve something to the fullest and it will be difficult for him to achieve success. This study aims to determine the relationship between self-confidence and assertive behavior in children aged 5-6 years at TK Negeri Pembina 1 Pekanbaru. This study is a quantitative study with a type of correlation research. The sampling technique used in this study is saturated samples with a sample of 90 people. The data collection technique used is the observation sheet. The data analysis techniques were used Pearson Product Moment Correlation techniques. Based on the results of hypothesis testing it is known from the correlation coefficient of rxy = 0.102 with a significance level of 0.039 <0.05. Thus it can be concluded that there is a relationship between self-confidence and assertive behavior. The level of the relationship is included in the very low category with the value of the determinant coefficient generated is 10%, it can be seen that self-confidence contributes 10% to assertive behavior.Keyword: Self-confidence, Assertive Behaviour